Dampak Teknologi Digital Anak Usia Dini dengan Kebutuhan Perlindungan Hukum Era Media Sosial - Arrizka Listiaga (Jurnal Hukum Lex Generalis, 2025)
Advances in information and communication technology have increased the involvement of children under the age of 13 in social media, such as creating creative content on TikTok and Instagram. To protect children from exploitation, Law No. 13 of 2003 on Manpower Article 69 prohibits child labor. However, this prohibition does not apply to positive digital activities of children. Discussions indicate that this inconsistency could lead to potential exploitation and consequences such as violations of the Child Protection Law. Compared to the US COPPA, Indonesian law needs to be revised to distinguish between exploitation and creative activities, ensure parental supervision, and protect children's privacy in the digital age.